2013
DOI: 10.1016/j.contraception.2013.04.038
|View full text |Cite
|
Sign up to set email alerts
|

What college women know, think and do about human papillomavirus (HPV) and HPV vaccine

Abstract: Participants were a convenience sample of college women (n=384) ages 18 to 26 attending a large, public university in Southern California. An electronic self-administered survey was utilized to collect data. The theory of planned behavior provided a framework for understanding the factors associated with vaccine uptake and with post-vaccine sexual behaviors. Results: College women had good HPV/HPV vaccine knowledge. Over 90% of vaccinees and non-vaccinees knew that Pap test is still needed after the vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 30 publications
6
25
2
Order By: Relevance
“…This study indicated that factors influencing intention include attitude toward obtaining the vaccine, subjective norm (perceived pressure from significant others in order to vaccinate), HPV/HPV vaccine knowledge, and age. Using the same theoretical framework, the study results are similar to prior studies conducted among young adults in Canada and America where the intention was predicted by the attitude and subjective norm [13,28,29]. In addition, a study conducted among Taiwanese undergraduate women reported that vaccination intention was associated with recommendations from others, vaccine cost, availability, and perceived disease severity, risks, and vaccination benefits [30].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…This study indicated that factors influencing intention include attitude toward obtaining the vaccine, subjective norm (perceived pressure from significant others in order to vaccinate), HPV/HPV vaccine knowledge, and age. Using the same theoretical framework, the study results are similar to prior studies conducted among young adults in Canada and America where the intention was predicted by the attitude and subjective norm [13,28,29]. In addition, a study conducted among Taiwanese undergraduate women reported that vaccination intention was associated with recommendations from others, vaccine cost, availability, and perceived disease severity, risks, and vaccination benefits [30].…”
supporting
confidence: 75%
“…The anonymous paper-based questionnaire titled HPV and HPV vaccine-related knowledge, attitudes, and behaviors was adapted and translated to Thai from the first author's prior study with college women in the USA [13]. The translated questionnaire was translated back by two persons -one researcher who earned her Doctorate Degree in nursing from the USA and one Thai-American citizen who earned her Master Degree in public administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial cross-sectional studies after vaccine approval showed limited positive associations between HPV-related knowledge and intention to be vaccinated against HPV in young female adults, 19-21 more recent investigations have shown that knowledge is not associated with interest in vaccination or vaccine uptake after adjustment for other factors. 18,22 Factually driven educational interventions targeting participant knowledge have shown to have some impact on intention to be vaccinated 7 but have not been associated with change in actual vaccine uptake. 9,10 Taken together, these studies suggest that a knowledgefocused approach may impact immediate vaccine intent, but does not appear to affect behavior.…”
Section: Comparison With Previous Interventionsmentioning
confidence: 98%
“…The present study showed that the proportion of students who received education on cervical cancer increased from 2011 to 2013 (Table 1). Although knowledge of cervical cancer and the HPV vaccination may not be directly linked to HPV vaccination uptake, as noted by Ratanasiripong et al, 8 many investigations have shown that knowledge of cervical cancer positively influences the rate of HPV vaccination uptake. [14][15][16][17] In the present study, the logistic regression model included factors of education and knowledge.…”
Section: Discussionmentioning
confidence: 97%